Efficacy of various post-moult feed supplementations in poultry: an empirical review. Issue 3 (1st September 2016) - Anwar, H.; Iftikhar, A.; Sohail, M.U.; Hussain, G.; Faisal, M.N.; Khan, J.A.; Bukhari, S.A.; Iqbal, Z.
Abstract : Based upon its economical perspective, the phenomenon of forced moulting in the poultry industry has become a common practice to increase the productivity and reproductive life span of birds. Different feed supplements, including vitamins, minerals, probiotics and prebiotics have been extensively used by poultry farmers for many years. In the last decade, researchers have reported advantageous effects of these supplements in improving different health biomarkers of post moult poultry birds. Therefore, including with these supplements in post moult feed is believed to exhibit better results than moulting alone. The current review is aimed at highlighting the empirical data available on the importance of various feed supplements that are considered favourable in ameliorating the health status of moulted poultry birds.